Targeted extracellular vesicle delivery systems employing superparamagnetic iron oxide nanoparticles. (15th October 2021) - Zhuo, Zewei; Wang, Jinghua; Luo, Yujun; Zeng, Ruijie; Zhang, Chen; Zhou, Weijie; Guo, Kehang; Wu, Huihuan; Sha, Weihong; Chen, Hao
Abstract: In the past decade, the study of extracellular vesicles (EVs), especially exosomes (50–150 nm) have attracted growing interest in numerous areas of cancer and tissue regeneration due to their unique biological features. A low isolation yield and insufficient targeting abilities limit their therapeutic applicability. Recently, superparamagnetic iron oxide nanoparticles (SPIONs) with magnetic navigation have been exploited to enhance the targeting ability of EVs. To construct targeted EV delivery systems engineered by SPIONs, several groups have pioneered the use of different techniques, such as electroporation, natural incubation, and cell extrusion, to directly internalize SPIONs into EVs. Furthermore, some endogenous ligands, such as transferrins, antibodies, aptamers, and streptavidin, were shown to enable modification of SPIONs, which increases binding with EVs. In this review, we summarized recent advances in targeted EV delivery systems engineered by SPIONs and focused on the key methodological approaches and the current applications of magnetic EVs. This report aims to address the existing challenges and provide comprehensive insights into targeted EV delivery systems. Statement of significance: Targeted extracellular vesicle (EV) delivery systems engineered by superparamagnetic iron oxide nanoparticles (SPIONs) have attracted wide attention and research interest in recent years. Such strategies employ external magnet fields to manipulate SPION-functionalized EVs remotely, aiming to enhance their accumulation and penetration in vivo. Although iron oxide nanoparticle laden EVs are interesting, they are controversial at present, hampering the progress in their clinical application. A thorough integration of these studies is needed for an advanced insight and rational design of targeted EV delivery systems. In this review, we summarize the latest advances in the design strategies of targeted EV delivery systems engineered by SPIONs with a focus on their key methodological approaches, current applications, limitation and future perspectives, which may facilitate the development of natural theranostic nanoplatforms. Graphical abstract: Image, graphical abstract